Memories of German Colonialism in Tanzania - Kirey, Reginald Elias (European Colonialism in Global Perspective, 2023)
The book documents the collective memories of German colonialism in Tanzania Mainland which formed part of the former Germany East Africa. It argues that German colonialism which ended with the First World War left cultural and communicative memories that have survived to the present. It reveals that the Germans are remembered differently by people from different parts of Tanzania due to the varied nature of German colonial activities or events.